The analysis of authenticity on destination loyalty mediated by heritage tourism - Ratih Anggraini; Windy Graciela Wang; Dessy Aliandrina (Universitas Merdeka Malang, 2024)
Heritage tourism is an attractive destination for many people because it has its own culture and characteristics. The city of Penang is one of the world's cultural heritage destinations which is listed on the World Heritage List by UNESCO as a cultural heritage destination and has preserved the culture that has existed for a long time. The majority of tourists who visit Penang City come from Indonesia. This research aims to analyze the influence of authenticity on destination loyalty mediated by heritage tourism in Penang City and analyze how each variable influences each other, is related, and has a positive and significant impact to each other. This research uses quantitative methods by determining the sample using the purposive sampling method. Data testing was carried out using the PLS-SEM test to test the hypothesis and the influence between variables in this research. The results of the research show that the authenticity of Penang City has a positive and significant influence on destination loyalty with heritage tourism as a mediation for Indonesian national tourists in Batam City. This shows that the authenticity of Penang City influences tourists' travel interests.